(untitled) (Al-Academy, 2020)
Art of legend was arisen out of pillars of theatre which casts light on those legends that were written to glorify powers and situations surpass level of human beings . So we find that legend was transformed through its doctrine sides over level of concept and realization on field of subjects where by which Greek theatre was founded . As soon as it was adopted by drama art as legendary ritual phenomena with its stories . With that modes of social , spiritual expressions were differentiated within communities , peoples over all different countries and civilizations . This explains us the apparent difference in cases of legends , alike if they were within thoughtful , social or cultural sides between civilizations . Since drama art is mirror of peoples that reduces inside it tribes , rites , religion celebrations and legendary tales . We find significant necessity to research , to uncover mechanisms of construct legend , from another hand to tackle it by some drama directors , who added aesthetic , creative conceptions for their drama shows through two notions which are legend and westernization Key words : Procedures of Westernization , legend , civilization , Iraqi theatre